Speed Control of DC Motor Using ACO Based FOPID Controller (International Journal of Innovative Research in Computer Science & Technology, 2020)
Direct current (DC) motors are widely used  because of their easily controllable and reliable access. DC  motors have many salient features that includes a wide  range of torque speed control, reliable operation with  greater efficiency and a greater starting torque and many  more. A nonlinear model for a DC motor can be  represented for considering all uncertainties and non linearities. In this paper, DC motor is studied which is  having a second order system. Many controllers are being  used for controlling speed of DC motor. An analysis is  carried out on mathematical model of DC motor whose  field is excited by an external or separate supply. Tuning of  FOPID parameters using Ant Colony Optimization  Technique (ACO) is discussed here.
Keywords: ACO; DC Motor; FOPID Controller; PID Controller; Swarm Intelligence